A systematic review and meta-analysis of carbohydrate benefits associated with randomized controlled competition-based performance trials. Issue 1 (December 2016) - Pöchmüller, Martin; Schwingshackl, Lukas; Colombani, Paolo; Hoffmann, Georg
Abstract Background Carbohydrate supplements are widely used by athletes as an ergogenic aid before and during sports events. The present systematic review and meta-analysis aimed at synthesizing all available data from randomized controlled trials performed under real-life conditions. Methods MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials were searched systematically up to February 2015. Study groups were categorized according to test mode and type of performance measurement. Subgroup analyses were done with reference to exercise duration and range of carbohydrate concentration. Random effects and fixed effect meta-analyses were performed using the Software package by the Cochrane Collaboration Review Manager 5.3. Results Twenty-four randomized controlled trials met the objectives and were included in the present systematic review, 16 of which provided data for meta-analyses. Carbohydrate supplementations were associated with a significantly shorter exercise time in groups performing submaximal exercise followed by a time trial [mean difference −0.9 min (95 % confidence interval −1.7, −0.2), p  = 0.02] as compared to controls. Subgroup analysis showed that improvements were specific for studies administering a concentration of carbohydrates between 6 and 8 % [mean difference −1.0 min (95 % confidence interval −1.9, −0.0), p  = 0.04]. Concerning groups with submaximal exercise followed by a time trial measuring power accomplished within a fixed time or distance, mean power output was significantly higher following carbohydrate load (mean difference 20.2 W (95 % confidence interval 9.0, 31.5), p  = 0.0004]. Likewise, mean power output was significantly increased following carbohydrate intervention in groups with time trial measuring power within a fixed time or distance (mean difference 8.1 W (95 % confidence interval 0.5, 15.7)p  = 0.04]. Conclusion Due to the limitations of this systematic review, results can only be applied to a subset of athletes (trained male cyclists). For those, we could observe a potential ergogenic benefit of carbohydrate supplementation especially in a concentration range between 6 and 8 % when exercising longer than 90 min.